Heart Rate Variability and Training Optimization in Sports: A Review of Foundations, Methods, and Practical Applications - Amine, NEHAOUA (Journal of Sport Science Technology and Physical Activities, 2026)
Heart rate variability (HRV) is a key indicator of autonomic regulation and adaptation to training. In sports, HRV monitoring helps evaluate internal load, recovery status, and prevent overtraining. This article presents the physiological foundations, main analytical methods, and practical applications of HRV for adjusting training loads and optimizing performance. Integrating HRV into athlete monitoring systems, combined with wearable technologies and artificial intelligence, enables real-time personalized tracking, making HRV a central tool in modern sports training management and performance optimization.